2018
DOI: 10.3390/su10051415
|View full text |Cite
|
Sign up to set email alerts
|

Structural Equation Model for Evaluating Factors Affecting Quality of Social Infrastructure Projects

Abstract: The quality of the constructed social infrastructure project has been considered a necessary measure for the sustainability of projects. Studies on factors affecting project quality have used various techniques and methods to explain the relationships between particular variables. Unexpectedly, Structural Equation Modeling (SEM) has acquired very little concern in factors affecting project quality studies. To address this limitation in the body of knowledge, the objective of this study was to apply the SEM app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
145
0
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(154 citation statements)
references
References 74 publications
2
145
0
7
Order By: Relevance
“…Therefore, this study confirmed that PLS-SEM could be an alternative approach for predicting behavioral intention in C-TAM-TPB models. However, it should be noted that, relatively, PLS-SEM has a great advantage over multiple linear regression in terms of convenience [29], flexibility [20], and other functions [30,31]. This is an initial study for the development of an Integrated Water System in the municipality of Mulanay.…”
Section: Discussion and Research Implicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, this study confirmed that PLS-SEM could be an alternative approach for predicting behavioral intention in C-TAM-TPB models. However, it should be noted that, relatively, PLS-SEM has a great advantage over multiple linear regression in terms of convenience [29], flexibility [20], and other functions [30,31]. This is an initial study for the development of an Integrated Water System in the municipality of Mulanay.…”
Section: Discussion and Research Implicationsmentioning
confidence: 99%
“…Further, aside from the assessment of each path coefficient through bootstrapping, in PLS-SEM, the significance of the indirect effects of each variable on endogenous variables can also be verified [30]. Moreover, the behavior of exogenous variables on endogenous variables can also be predicted in PLS-SEM using a blindfolding process [31]. This can serve as a guide to improve the model.…”
Section: Research Framework Variables and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…For our Structural Equation Modelling analysis, the Smart-PLS (v.3.2.7) (GmbH, Boenningstedt, Germany). was the software instrument [57] whose effectiveness for casual analysis is recognized and widely used [58].…”
Section: Structural Equation Model (Sem)mentioning
confidence: 99%
“…Shahid Hussain et al, (2018) applied SEM approach to identify the critical factors affecting quality in social infrastructure projects. The authors developed a quantitative approach using smart-PLS version 3.2.7.…”
Section: Literature Surveymentioning
confidence: 99%